THE APPLICATION OF THE RESPONSIBILITY PRINCIPLE IN THE MANAGEMENT OF TANNERY IN SUKAREGANG KAB. GARUT CONNECTED WITH LAW REGULATIONS - Ghausya Syafanah Syifa (Universal Journal, 2026)
The principle of responsibility is one of the fundamental principles of Good Corporate Governance (GCG), which requires every company or business entity to assume responsibility for the welfare of society and the protection of the environment. The GCG system has been implemented in various regions of Indonesia, including Garut Regency, where it is regulated under regional legislation. This study aims to examine the implementation of the principle of responsibility by tannery business operators in Sukaregang, Garut, in accordance with applicable laws and regulations, as well as to analyze the sanctions imposed on business operators whose activities have caused long-term environmental pollution. This research employs a normative juridical approach using library research as the primary data source. The collected data were analyzed qualitatively. The findings reveal that the principle of responsibility as stipulated in Garut Regency Regional Regulation No. 16 of 2017 concerning Corporate Social and Environmental Responsibility has not been fully implemented by tannery business operators in the Sukaregang area. Furthermore, administrative and criminal sanctions are applicable to business operators who fail to comply with the provisions of the regulation.